2017
DOI: 10.1002/mana.201600399
|View full text |Cite
|
Sign up to set email alerts
|

A unified method for boundedness in fully parabolic chemotaxis systems with signal‐dependent sensitivity

Abstract: This paper deals with the Keller–Segel system {ut=Δu−∇·false(uχ(v)∇vfalse),x∈Ω,t>0,vt=Δv+u−v,x∈Ω,t>0,where Ω is a bounded domain in Rn with smooth boundary ∂Ω, n≥2; χ is a nonnegative function satisfying χfalse(sfalse)≤K(a+s)−k for some k≥1 and a≥0. In the case that k=1 and a=0, Fujie established global existence of bounded solutions under the condition 0false01, Winkler asserted global existence of bounded solutions for arbitrary K>0. However, there is a gap in the proof. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 14 publications
(70 reference statements)
0
23
0
Order By: Relevance
“…Proof For a function f:Ω×[0,T)R putting ffalse(x,tfalse):=ffalse(x,λtfalse) for false(x,tfalse)Ω×(0,Tλ), we see that truevλ satisfies truerightleftfalse(truevλfalse)t=normalΔtruevλtruevλ+trueu,leftxnormalΩ,0.33emt()0,Tλ,lefttruevλ·ν=0,leftxnormalΩ,0.33emt()0,Tλ,lefttruevλ(x,0)=v init (x),leftxnormalΩ.Thus since the mass conservation yields that 0trueΩu(·,λt)=m for all t(0,Tλ) and any λ>0, we infer from (see also [, Lemma 2.1]) that trueη defined as satisfies truerigh...…”
Section: Preliminariesmentioning
confidence: 99%
See 4 more Smart Citations
“…Proof For a function f:Ω×[0,T)R putting ffalse(x,tfalse):=ffalse(x,λtfalse) for false(x,tfalse)Ω×(0,Tλ), we see that truevλ satisfies truerightleftfalse(truevλfalse)t=normalΔtruevλtruevλ+trueu,leftxnormalΩ,0.33emt()0,Tλ,lefttruevλ·ν=0,leftxnormalΩ,0.33emt()0,Tλ,lefttruevλ(x,0)=v init (x),leftxnormalΩ.Thus since the mass conservation yields that 0trueΩu(·,λt)=m for all t(0,Tλ) and any λ>0, we infer from (see also [, Lemma 2.1]) that trueη defined as satisfies truerigh...…”
Section: Preliminariesmentioning
confidence: 99%
“…Moreover, Fujie–Senba established global existence and boundedness in the two‐dimensional parabolic‐elliptic system with more general sensitivity function. On the other hand, also in the parabolic‐parabolic case, it was shown that some smallness condition for χ implies global existence and boundedness; in the case that χfalse(vfalse)=χ0v (χ0>0) Winkler obtained global existence of classical solutions under the condition that χ0<2n and Fujie established boundedness of these solutions; in the case that χfalse(vfalse)χ0false(a+vfalse)k (χ0>0, a0, k>1) some smallness condition for χ 0 leads to global existence and boundedness (); recently, Fujie–Senba showed global existence and boundedness of radially symmetric solutions to the parabolic‐parabolic system with more general sensitivity function and small λ in a two‐dimensional ball.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations